1979
DOI: 10.1093/ajcn/32.12.2484
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of iron from breakfast meals

Abstract: The absorption of nonheme iron from nine common Western type breakfasts was studied in 129 subjects using extrinsic labeling with radioiron. In one group the iron absorption from a continental type of breakfast served with coffee was standardized against the absorption from a reference dose of derrous ascorbate (3 mg Fe). In all subsequent experiments the absorption from this breakfast was compared with one of the other breakfast meals served on alternate days and each labeled with a different radioiron isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
2
5

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(63 citation statements)
references
References 4 publications
0
56
2
5
Order By: Relevance
“…It has long been known that tea has a negative impact on the absorption of non-haem iron in the diet (Disler et al, 1975;Rossander et al, 1979;Hallberg & Rossander, 1982), and some studies have shown a negative correlation between tea consumption and haemoglobin (Merhav et al, 1985) or serum ferritin (Galan et al, 1985) concentrations. However, other studies have found the relationship to be ambiguous (Brussaard et al, 1997) or non-existent (Soustre et al, 1986;Galan et al, 1998;Root et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that tea has a negative impact on the absorption of non-haem iron in the diet (Disler et al, 1975;Rossander et al, 1979;Hallberg & Rossander, 1982), and some studies have shown a negative correlation between tea consumption and haemoglobin (Merhav et al, 1985) or serum ferritin (Galan et al, 1985) concentrations. However, other studies have found the relationship to be ambiguous (Brussaard et al, 1997) or non-existent (Soustre et al, 1986;Galan et al, 1998;Root et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Fibre intake decreased with age (P`0.001, r 2 0.05) so the association found with iron status could also re¯ect the fact that the relatively healthy older people (with good teeth, etc) have better haematological status indices. Rossander et al (1979) reported that consumption of tea with breakfast reduced iron absorption to less than half. Ninety ®ve per cent of the NDNS participants drank tea and a little contrary to expectations, tea had a signi®cant negative association for men only, and only on two of the eight measures of iron status under consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have not found a consistent relationship between iron intake and iron status, and it seems that a number of other factors in the diet are important, including enhancers (such as vitamin C and haem iron) and inhibitors (such as calcium and non-starch polysaccharides) of iron absorption (Hallberg, 1981;Hallberg et al, 1992). While there are a number of studies describing iron absorption from test meals of different compositions (Moore & Dubach, 1951;Martinez-Torres et al, 1974;Rossander et al, 1979;Oski & Landaw, 1980;Stekel et al, 1986;Davidsson et al, 2000), there is far less information on the relationship between the dietary intake of enhancers and inhibitors of iron absorption and iron status in free-living populations. As part of the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC) we have collected data on haemoglobin and ferritin levels at 18 months along with detailed dietary information.…”
Section: Introductionmentioning
confidence: 99%